Species Diversity of Urban Birds in Biratchowk, Morang, Nepal (Sukuna Journal, 2026)
Urban birds are species that thrive in city habitats and serve as indicators of urban environmental change. The present study was conducted to explore the diversity of urban birds in Biratchowk to develop baseline information for future research to understand how ongoing urban growth may be influencing their diversity, which will be helpful for future research. The data were collected during March to May of 2025 by using the point count method. A total of 24 species representing 23 genera, 16 families, and 7 orders were recorded. The order Passeriformes contributed the highest number of species (10), and Bucerotiformes and Charadriiformes each had a single species in the study area. The ecological indices showed moderate species diversity (H = 2.81), high evenness (E = 0.88), and semi-disturbed richness (D = 3.96). This study revealed that dense human settlement, limited vegetation, and scarcity of suitable nesting sites are associated with only moderate species diversity in the Biratchowk area.